MicroCT-based phenomics in the zebrafish skeleton reveals virtues of deep phenotyping in a distributed organ system - Hur, Matthew; Gistelinck, Charlotte A; Huber, Philippe; Lee, Jane; Thompson, Marjorie H; Monstad-Rios, Adrian T; Watson, Claire J; McMenamin, Sarah K; Willaert, Andy; Parichy, David M; Coucke, Paul; Kwon, Ronald Y (eLife, 2017)
Phenomics, which ideally involves in-depth phenotyping at the whole-organism scale, may enhance our functional understanding of genetic variation. Here, we demonstrate methods to profile hundreds of phenotypic measures comprised of morphological and densitometric traits at a large number of sites within the axial skeleton of adult zebrafish. We show the potential for vertebral patterns to confer heightened sensitivity, with similar specificity, in discriminating mutant populations compared to analyzing individual vertebrae in isolation. We identify phenotypes associated with human brittle bone disease and thyroid stimulating hormone receptor hyperactivity. Finally, we develop allometric models and show their potential to aid in the discrimination of mutant phenotypes masked by alterations in growth. Our studies demonstrate virtues of deep phenotyping in a spatially distributed organ system. Analyzing phenotypic patterns may increase productivity in genetic screens, and facilitate the study of genetic variants associated with smaller effect sizes, such as those that underlie complex diseases.
Keywords: microCT; phenomics; bone; skeleton; mineralization; imaging